Template for evaluating dexterity in non-surgical periodontal, prophylactic, and cosmetic phantom head laboratory instrumentation - Adamu, V. E.; Eneojo, Ndidamaka Ijeoma Favour (Orapuh Journal, 2023)
The assessment of non-surgical periodontal, prophylactic, and cosmetic instrumentation in the laboratory requires an objective evaluation machinery to elicit the right feedback. We have developed this template with the hope that dental phantom head laboratory training instructors would adopt it to give their students fair and equitable feedback to laboratory instrumentation.